Prevalence of heart failure and the diagnostic value of MR‐proANP in outpatients with type 2 diabetes. Issue 3 (5th December 2018) - Jensen, Jesper; Schou, Morten; Kistorp, Caroline; Faber, Jens; Hansen, Tine W.; Jensen, Magnus T.; Andersen, Henrik U.; Rossing, Peter; Vilsbøll, Tina; Jørgensen, Peter G.
Abstract : The prevalence of heart failure (HF) in patients with type 2 diabetes (T2DM) is debatable and no data exist concerning the diagnostic value of mid‐regional pro‐atrial natriuretic peptide (MR‐proANP). We aimed to identify HF prevalence and evaluate the diagnostic value of MR‐proANP in outpatients followed in two specialized diabetes clinics. HF was pre‐defined as HF with reduced ejection fraction (HFrEF) and HF with preserved ejection fraction (HFpEF). The prevalence of HFrEF and HFpEF was 2.4% and 17.5%, respectively. An MR‐proANP <60 pmol/L ruled out HFrEF in the total population (n = 806) and in patients reporting dyspnea (n = 311) with a sensitivity of 94.7% and 87.5%, a negative predictive value of 99.7% and 99.0%, a specificity of 39.5% and 33.0%, and a positive predictive value of 3.6% and 3.3%, respectively. In a multivariable model including age, sex, T2DM duration, albuminuria, uncontrolled systolic blood pressure, abnormal electrocardiogram and ischaemic heart disease for diagnosis of HF in patients reporting dyspnea, adding MR‐proANP increased the area under the curve from 0.69 to 0.78 ( P < 0.001). In conclusion, HFrEF was rare among outpatients with T2DM. MR‐proANP rules out HFrEF and contributes independent information relevant to diagnosis of HF in patients reporting dyspnea.